A synergistic consequence of catalyst dosage, pH solution and reactive species of Fe-doped CdAl2O4 nanoparticles on the degradation of toxic environmental pollutants. (March 2023) - Rajesh, G.; Kumar, P. Senthil; Akilandeswari, S.; Rangasamy, Gayathri; Mandal, Aindrila; Shankar, V. Uma; Ramya, M.; Nirmala, K.; Thirumalai, K.
Abstract: Industrial wastewater treatment techniques are one of the biggest challenges of the scientific community that necessitate an increased consciousness to address water scarcity worldwide. Herein, an eco-friendly and cost-effective process was demonstrated to cope with tannery, textile and pharmaceutical dye wastes through the co-precipitation of highly reusable Fe-doped CdAl2 O4 samples. The XRD studies exposed the space group R 3 ‾ with no secondary phase step being found for all samples. The outcomes of optical absorbance spectra demonstrate that Fe doping diminished the energy gap from 3.66 to 1.67 eV. HR-TEM images of existing spherical particles and some of the particles' rod-like structures with little agglomeration were found for Fe (0.075 M) doped CdAl2 O4 nanoparticles. The PL emission outcomes show that Fe doping effectively prevented the charge carrier's recombination in CdAl2 O4 during photocatalysis. All Fe-doped CdAl2 O4 samples demonstrated higher photodegradation behaviors towards the effectual degradation of both dye solutions as compared to pure CdAl2 O4 samples. Particularly, Fe (0.075 M)-doped CdAl2 O4 samples exhibited improved photodegradation performance of 93 and 95% for both dye solutions. The amount of photodegradation was noticed to rely on dye pH, irradiation time, catalyst dosage, initial dye amount, and reactive species. The recyclability of the Fe (0.075 M) doped CdAl2 O4 nanoparticles denotes that 78 and 82% of BB and BG were removed up to the 6th run of usage. The outcomes of trapping tests, . OH − and h + radicals were the major Scavenging in the photodegradation reaction. COD studies affirmed the whole mineralization of BB and BG dye molecules. It is expected that our present examination could offer to improve various spinal oxide materials for the photodegradation activity of pharmaceutical contaminants and environmental issues and can also resolve energy storage applications. Graphical abstract: Image 1 Highlights: A novel pure and Fe-doped CdAl2 O4 nanoparticles fabricated by chemical co-precipitation approach. Fe (0.075 M) doped CdAl2 O4 catalyst removed 94 and 96% for BB and BG dyes under visible illumination. ·OH − and h + radicals were the major scavenging species in the degradation of the two Azo dyes. Fe (0.075 M) doped CdAl2 O4 catalyst showed 78 and 84% degradation efficiencies in six consecutive runs.